Impact of residential demand response on the integration of intermittent renewable generation into the smart grid - Soares Moura, Pedro; López López, Gregorio; Moreno Novella, Jose Ignacio; Almeida, Anibal T. de (Sin editorial (Coimbra, Portugal))
The deployment of renewable generation infrastructures, such as photovoltaic and wind power, have been leading to a dramatically increase on the variability and randomness of energy generation, thus increasing the complexity of the grid management. At the same time, the energy consumption in households has been steadily growing during the last few years, driving the development of real-time monitoring and control systems to achieve energy and costs savings. Such systems could also be used to ensure optimization objectives and to improve the grid reliability, changing the demand profile to match the renewable generation. The European FP7 project ENERsip has developed a novel energy monitoring and control system integrated at the edge of the service-oriented M2M-based platform for energy efficiency within energypositive neighbourhoods which provides the required communications and processing capabilities to operate DR (Demand Response) programs with the aim of ensuring the generation and consumption matching. This paper presents the architecture and DR services ensured by ENERsip, as well as the potential impacts of such DR system to ensure the proper integration of renewable generation into the electric grid.
Capítulos en libros
Keywords: Instituto de Investigación Tecnológica (IIT)